(untitled) (NAU Journal of Technology and Vocational Education, 2026)
This study examined the relevance of Computer-Based Testing (CBT) usage on academic performance of Business Education students at Ebonyi State University. Two purposes of study and research questions guided the study. A descriptive survey research design was adopted, with a population of 216 respondents. No sampling was employed as the researchers used census population. Data were collected using a researcher instrument titled "Relevance of Computer Based Testing on Academic Performance" (RCBTAP), which was validated and yielded a index reliability coefficient of 0.81 using Cronbach Alpha. Mean and standard deviation were used to answer research questions. Findings revealed that respondents agreed on all seven identified benefits of Computer Based Testing including enhanced security, instant scoring, administrative efficiency, and innovative assessment items. Additionally, all twelve identified challenges such as inadequate funding, poor power supply, unstable internet connectivity, computer illiteracy, and psychological stress were affirmed as obstacles to effective Computer Based Testing implementation. The study concluded that while Computer Based Testing holds significant potential for improving academic performance in Business Education, addressing infrastructural deficits and capacity building is essential for optimal implementation. Recommendations included increased funding for CBT infrastructure, integration of computer literacy training, and provision of technical support.